2011
DOI: 10.1007/s00534-011-0377-6
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of laserphyrin compared with photofrin in photodynamic therapy for bile duct carcinoma

Abstract: Background The aim of this study was to compare the effects of laserphyrin-PDT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…36,37 Previous our studies using cultured cells showed that the main effect of PDT is apoptosis, evidenced by assays that measured either DNA fragmentation or chromatin condensation. 17,18 PDT induced NOZ cell death by apoptosis, detected in the Hoechst 33342-stained sections, in a light dose-dependent manner. Based on this preliminary study, the photosensitizer dose and light dose were already determined, which was applied in the present study.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…36,37 Previous our studies using cultured cells showed that the main effect of PDT is apoptosis, evidenced by assays that measured either DNA fragmentation or chromatin condensation. 17,18 PDT induced NOZ cell death by apoptosis, detected in the Hoechst 33342-stained sections, in a light dose-dependent manner. Based on this preliminary study, the photosensitizer dose and light dose were already determined, which was applied in the present study.…”
Section: Discussionmentioning
confidence: 87%
“…The estimated talaporfin sodium dose was 20 μg/ml as determined by our preliminary study. 18 The administered solution was incubated at 37°C for 3 hours, later decantated and then washed three times in PBS. To induce LD 50 PDT conditions, a laser power of 12 J/cm 2 was chosen to irradiate the NOZ cells.…”
Section: Photodynamic Therapymentioning
confidence: 99%
See 3 more Smart Citations